Pengambilan Keputusan Melajang pada Perempuan Etnis Madura: Sebuah Studi Fenomenologis - Alfarisi, M Salman; Bawono, Yudho (Universitas Semarang, 2024)
There are many people who do the Madura tradition of early marriages but over time social changes they also affect in deciding about life to delaying marriage. The delay marriage or people often call people unmarried as single. Single is a condition in which a man/woman has not yet and does not have a marriage. This research was intended to find out how the decision was to postpone marriage on women in Madurese. This study uses qualitative methods performed on two participants with data collection done by purposive sampling means mature female participants who are not married aged 40-60 years. Research using semi-structured interviews with the Interpretative Phenomenological Analysis (IPA). IPA helps the researcher in interpreting the subjective meaning of the participant in relation to her experience in decision making. This study found that the reason not to marry because of having trauma with the past, knowing the divorced parents, have had a romantic relationship but failed to marry, and have not found a suitable partner.